Between the colossal and the catastrophic: Planetary urbanization and the political ecologies of emergent infectious disease. (August 2022) - Brenner, Neil; Ghosh, Swarnabh
Against the backdrop of contemporary debates on the transcendence of city-centric epistemologies in urban theory, this article proposes a theoretical framework for exploring the connections between processes of planetary urbanization and the political ecologies of emergent infectious disease. Following a brief overview of research on cities and the coronavirus pandemic, we elaborate a critical interrogation and heterodox synthesis of two distinct lines of investigation—(1) research by Roger Keil and his collaborators on the embeddedness of emergent infectious diseases within processes of extended urbanization and (2) work by radical epidemiologist Rob Wallace and his colleagues, which productively situates emergent infectious diseases in relation to the geographies and political ecologies of agribusiness under neoliberalizing capitalism. We direct attention to the ways in which processes of planetary urbanization are remaking the human and nonhuman geographies of non-city spaces, causing infectious pathogens to be unmoored from previously localized ecosystems and catapulted into broader territories of circulation. This line of analysis requires rigorous application of dialectical methods that can illuminate the internal relations through which cities dynamically co-evolve and co-transform with the non-city spaces, more-than-human territories, and multispecies political ecologies that support their metabolic operations, including at the microbiological scale of novel pathogens. The elaboration of such an approach yields an interpretation of the urbanization/emergent infectious disease nexus as a medium and expression of the agro-ecological crisis tendencies of neoliberal capitalism. A concluding section outlines three emergent arenas of agro-industrial transformation in which processes of extended urbanization have created new spatial configurations and infrastructural pathways for the production and proliferation of emergent infectious diseases.